Determinant of smallholder farmer labor allocation decisions in Uganda - Bagamba, Fred; Burger, Kees; Kuyvenhoven, Arie (International Food Policy Research Institute, 2009)
Although there is growing evidence of the increasing role of nonfarm activities in rural livelihoods, there is still relatively little empirical evidence regarding the factors that influence smallholder farmers to diversify into nonfarm activities. This study analyses the factors that influence household labor allocation decisions and demand for farm labor in Uganda. Data were collected from 660 households in three banana-based production zones with divergent production constraints and opportunities. The determinants of demand for hired labor were estimated with the Tobit model. Linear regression was used to estimate reduced-form equations for the time-allocation decisions of household members. Our findings show that household members respond positively to increases in wages, suggesting that they respond to economic incentives. Increased wage rates negatively affect the use of hired labor, but household size has no effect on the use of hired labor, indicating that the economic rationing of labor hiring has more to do with the market wage than family size or composition. Education and road access have positive effects on the amount of time allocated to off-farm activities. Access to off-farm opportunities, however, takes away the most productive labor from farm production. These findings suggest that investment in road infrastructure and education suited to smallholder production needs could help alleviate bottlenecks in labor markets and improve resource allocation between farm and nonfarm sectors.